Ecocentric and anthropocentric policies and crises in climate/environment, finance and economy: Implications of the emerging green policy of the Obama administration for Africa’s sustainable development - Richard Ingwe; Joseph C. Ebegbulem; C. C. C. Ikeji (African Journal of Environmental Economics and Management, 2013)
Advanced economies responded to recent global financial meltdown and economic recession by implementing “green” economic stimulus packages concentrating on environmentally-friendly and sustainable technologies. We examined this emerging paradigm against Sub-Saharan Africa’s under-development (prolonged poverty, economic stagnation/decline, weak structures, processes, institutions and attitudes required for accelerating economic growth; practice of electoralism: power derivation through elections without democratic ingredients), exclusion of stakeholders including civil society from policy, thereby depriving society innovations and resources contributed by civil society elsewhere to socio-economic development. We used desk research and descriptive methods to analyze secondary data based on increasing civil society involvement in development processes under emerging paradigm of partnership, governance, climate change, global financial crisis. We showed that past actions: unbridled pursuit of anthropocentric policy that ignored ecocentric measures led to crises (environmental-climate degradation, and recently global financial meltdown and economic recession), thereby worsening existing challenges. We recommend that African nations adopt the emerging green policy thereby increasing their chances of benefiting from the assistance of Governments. The promotion of green development policy in Africa is of urgent need and imperative.